2017
DOI: 10.1097/tp.0000000000001076
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cellular Rejection With a Cell-Based Assay

Abstract: Background Allospecific CD154+T-cytotoxic memory cells (CD154+TcM) predict acute cellular rejection (ACR) after liver or intestine transplantation (LTx, ITx) in small cohorts of children and can enhance immunosuppression management, but await validation and clinical implementation. Methods To establish safety and probable benefit, CD154+TcM were measured in cryopreserved samples from 214 children <21 years (NCT#1163578). Training set samples, n=158, were tested with research-grade reagents and 122 independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Quantification of donor‐specific alloimmune responses : The proportion of alloreactive CD8 + memory T cells was assessed in cryopreserved PBMCs collected immediately before Treg infusion, and 7 days and 1 month afterward, employing the U.S. Food and Drug Administration (FDA)–approved Pleximmune test . This assay uses flow cytometry to quantify the number of recipient CD8 + CD45RO + memory T cells expressing CD154 following 16 hours of culture with surrogate donor PBMCs (matched to donor at a minimum of one antigen each at human leukocyte antigen [HLA]‐A, ‐B, and ‐DR loci or 6‐loci mismatched third‐party PBMCs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of donor‐specific alloimmune responses : The proportion of alloreactive CD8 + memory T cells was assessed in cryopreserved PBMCs collected immediately before Treg infusion, and 7 days and 1 month afterward, employing the U.S. Food and Drug Administration (FDA)–approved Pleximmune test . This assay uses flow cytometry to quantify the number of recipient CD8 + CD45RO + memory T cells expressing CD154 following 16 hours of culture with surrogate donor PBMCs (matched to donor at a minimum of one antigen each at human leukocyte antigen [HLA]‐A, ‐B, and ‐DR loci or 6‐loci mismatched third‐party PBMCs).…”
Section: Methodsmentioning
confidence: 99%
“…PBMCs collected immediately before Treg infusion, and 7 days and 1 month afterward, employing the U.S. Food and Drug Administration (FDA)-approved Pleximmune test. 13,14 This assay uses flow cytometry to quantify the number of recipient CD8 + CD45RO + memory T cells expressing CD154 following 16 hours of culture with surrogate donor PBMCs (matched to donor at a minimum of one antigen each at human leukocyte antigen [HLA]-A, -B, and -DR loci or 6-loci mismatched thirdparty PBMCs). Similar experiments were conducted to quantify the frequency of CD154-positive memory CD8 + T cells following culture with an overlapping peptide mix of CMV pp65 antigen.…”
Section: Quantification Of Donor-specific Alloimmune Responses: the Pmentioning
confidence: 99%
“…Determining the risk of renal transplant rejection can lead to early diagnosis and intervention and enhance graft survival. Previous studies have shown that enhanced donor-specific alloreactivity measured with allospecific CD154-expressing T-cytotoxic memory cells (CD154 þ TcM) predicts ACR after liver or intestine transplantation in children [1][2][3]. This FDA-approved test has a sensitivity and specificity approaching or exceeding 80% [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all liver donors died from certain diseases, and some donors had critical diseases and deteriorating organ functions, including that of the liver. These factors significantly affect the post-transplant recovery of graft functions [ 2 ]. Clinically, it remains a main challenge to find a rapid and accurate approach to evaluate the function of transplanted livers and to predict the incidence of post-transplant complications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%